Evaluation of the relationships and uncertainties of airborne and ground-based sea ice surface temperature measurements against remotely sensed temperature records. Issue 1 (31st December 2022) - Fan, Pei; Zhao, Xi; Qu, Meng; Yan, Zhongnan; Chen, Ying; Liang, Zeyu; Pang, Xiaoping
ABSTRACT: Sea ice surface temperature (IST) is an important indicator of environmental changes in the Arctic Ocean. In this study, the relative performance of four mainstream IST records, i.e. airborne IST, infrared radiometer measured IST (IR IST), longwave radiation derived IST (LWR IST), and snow and ice mass balance array buoy derived IST (Buoy IST), were evaluated against the MODIS IST product. Bias, standard deviation (STD), and root mean square error (RMSE) were used to evaluate the data quality. Results revealed that airborne IST had the best accuracy, which was 0.21 K colder than MODIS IST, with STD of 1.46 K and RMSE of 1.47 K. Ground-based ISTs were biased with each other but all warmer than the MODIS IST. The IR IST had the best overall accuracy (bias = 0 .55 K; STD = 1 .52 K; RMSE = 1 .61 K), while the LWR IST was the noisiest measurement with the largest outlier data percent. Besides, co-located IR and LWR ISTs were more consistent than any type of evaluated IST against MODIS IST (correlation coefficient = 0 .99). Airborne and IR ISTs are thus the premier choice for monitoring the rapidly changing Arctic sea ice, together with satellite observations.